Analisis Peran Pondasi Umpak terhadap Respons Seismik Struktur Rumoh Aceh sebagai Upaya Mitigasi Risiko Gempa di Wilayah Aceh - Hildayani, Cut Sitti Rafidatul; Sabilla, Arissa; Yusri, Queen Monalisa; Hawari, Rifat Aditya (Universitas Iskandar Muda, 2026)
Aceh is a region with a high level of earthquake vulnerability due to the influence of regional tectonic activities. This condition requires the implementation of disaster mitigation concepts to reduce the risk of building damage and casualties. Rumoh Aceh is a traditional Acehnese house characterized by a wooden elevated structure supported by umpak foundation. This study analyzes the role of umpak foundation in the seismic response of Rumoh Aceh as an effort to mitigate earthquake risks in the Aceh region. The study employs a literature review method with a descriptive-qualitative analysis approach focusing on structural characteristics and seismic behavior of the building. The results indicate that the umpak foundation contributes to improving structural flexibility, reducing the transfer of seismic forces from the ground to the superstructure, and supporting natural energy dissipation mechanisms through relative movement at the column bases. The Rumoh Aceh structure exhibits a base shear force of 110 kN, while the reinforced concrete building reaches 343.75 kN. The umpak foundation demonstrates a strong relationship with modern earthquake disaster mitigation principles, particularly in reducing structural vulnerability. This research is expected to serve as a reference for developing earthquake risk mitigation concepts based on local wisdom in Aceh region.